Prosedur Penerbangan Pesawat Terjadwal Dan Pelanggarannya Ditinjau Dari Konvensi Chicago 1944 - Soumeru, Christi M P; Tuhulele, Popi; Hanafi, Irma Halima (Faculty of Law Universitas Pattimura, 2024)
Airspace violations by foreign aircraft according to international law are emphasized in several conventions and international agreements, one of which is the 1944 Chicago Convention on civil aviation. As in the case that occurred in 2019, where South Korea violated North Korea's airspace, the 1944 Chicago Convention also asserts that foreign state aircraft are not allowed to fly over or land in the territorial territory of another state without authority based on a special agreement or similar from the underlying state. The research method used is normative juridical. In processing and analyzing legal materials, the first step involves qualitative examination of collected primary, secondary, and tertiary legal materials, which are then categorized. These legal materials are reviewed using applicable international conventions to obtain a synchronized picture of all legal materials. Once the legal materials are synchronized with one another, they are further analyzed to address the issues raised in this writing. The research results indicate that the regulation of scheduled aircraft flight procedures is governed by the 1944 Chicago Convention, whereby a country whose airspace is traversed by scheduled commercial civil aircraft must ensure the safety of such civil aircraft. Several steps must be followed by the state party to prevent airspace violations by foreign aircraft, including issuing warnings, intercepting or intercepting the aircraft, and conveying relevant information regarding the warning to the scheduled aircraft such as aircraft identification, flight type, route taken, purpose of arrival, and so on. The form of state responsibility for North Korea's warning shots and firing at South Korea's commercial aircraft (Korean Airlines) is regulated under the 1944 Chicago Convention and other conventions.